2005
DOI: 10.1097/01.hjh.0000160216.86597.ff
|View full text |Cite
|
Sign up to set email alerts
|

Nebivolol decreases oxidative stress in essential hypertensive patients and increases nitric oxide by reducing its oxidative inactivation

Abstract: The findings of the present study indicate that nebivolol, through its antioxidant properties, increases NO also by decreasing its oxidative inactivation.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

3
64
1
1

Year Published

2005
2005
2023
2023

Publication Types

Select...
8
2

Relationship

0
10

Authors

Journals

citations
Cited by 110 publications
(69 citation statements)
references
References 39 publications
3
64
1
1
Order By: Relevance
“…This is consistent with earlier studies that indicated an antioxidant benefit for nebivolol through inhibition of NAD(P)H oxidase activity, 12,13 as well with a very recent study that demonstrated that nebivolol decreases oxidative stress in patients with essential hypertension. 21 However, it has been demonstrated that an acute infusion of antioxidant (ascorbic acid) improved vasodilation equally in black and white subjects. 22 This suggests that the difference in oxidative stress alone may not be sufficient to explain the differences in endothelial function of blacks and whites.…”
Section: Discussionmentioning
confidence: 99%
“…This is consistent with earlier studies that indicated an antioxidant benefit for nebivolol through inhibition of NAD(P)H oxidase activity, 12,13 as well with a very recent study that demonstrated that nebivolol decreases oxidative stress in patients with essential hypertension. 21 However, it has been demonstrated that an acute infusion of antioxidant (ascorbic acid) improved vasodilation equally in black and white subjects. 22 This suggests that the difference in oxidative stress alone may not be sufficient to explain the differences in endothelial function of blacks and whites.…”
Section: Discussionmentioning
confidence: 99%
“…Third-generation β-blockers also have neutral or favorable effects on lipid parameters [106,109,111]. Representative older and third-generation β-blockers have demonstrated antioxidant properties, including the ability to scavenge ROS, but thirdgeneration agents have shown these effects more consistently [111,[113][114][115][116].…”
Section: Mechanismsmentioning
confidence: 99%
“…Indeed, treatment strategies to increase bioavailable NO have been shown to protect against renal damage in several rodent models of RAAS and SNS-mediated renal sclerosis [9,10,11,12,13]. In this context, beta-blockers are known to suppress both the SNS and RAAS [14,15,16,17,18,19]. Nebivolol is a third-generation β 1 -adrenergic blocker with distinct pharmacologic and pharmacodynamic properties compared with other agents in its class [16].…”
Section: Introductionmentioning
confidence: 99%